Correlation of systemic immune-inflammation Index with surgical necrotizing enterocolitis - Feng, Wei; Hou, Jinping; Xiang, Chenzhu; Die, Xiaohong; Sun, Jing; Guo, Zhenhua; Liu, Wei; Wang, Yi (Frontiers in Pediatrics, 2022)
Background: Systemic Immune-Inflammation Index (SII), known as an easy, economical and useful marker, correlates with the severity of inflammatory response. However, the usefulness of SII in necrotizing enterocolitis (NEC) remains unclear. Therefore, we evaluated the correlation of SII at NEC diagnosis and subsequent surgery. Methods: Retrospective review of 131 neonates with NEC in a tertiary-level pediatric referral hospital was conducted with assessments of demographic data, general blood examination results at NEC diagnosis, treatment strategies and clinical outcomes. The receiver operating characteristic (ROC) curve determined the optimal cut-off values of SII, platelet-to-lymphocyte ratio (PLR), and neutrophil-to-lymphocyte ratio. Univariate/multivariate logistic regression analysis and ROC curve were conducted to evaluate the predictive significance of SII in identifying the patients who eventually received surgery. Additionally, NEC-related deaths were assessed. Results: Overall, 49 (37.4%) cases received surgical intervention and mortality was 12.3% (14/131). The area under ROC curve of SII at NEC diagnosis to predict subsequent surgery was 0.833 (optimal cut-off value: 235.85). The SII value in surgical intervention group was significantly higher than that in medical treatment group (332.92 ± 158.52 vs 158.84 ± 106.82, P < 0.001). Independent influencing factors for surgical NEC were SII (95% confidence interval [CI]: 4.568 ~ 36.449, odds ratio [OR]:12.904, P < 0.001) and PLR (95% CI: 1.071 ~ 7.356, OR:2.807, P=0.036). SII ≤ 235.85 could identify patients at high risk for surgery, with 87.76% sensitivity, 73.17% specificity, outperformed PLR. Furthermore, mortality was significantly higher in patients with SII ≤ 235.85 than those with SII > 235.85 (20.0% vs 1.5%, P < 0.001). Conclusion: SII and PLR at NEC diagnosis were independent influencing factors for subsequent surgery. SII ≤ 235.85 may be a useful predictive marker for the identification of surgical NEC and mortality.